Dirty money? The politics of representation in Cuban revolutionary banknotes. Issue 2 (26th May 2020) - Cabrera Arús, María A.
Abstract : This article examines the visual politics of Cuban postrevolutionary banknotes, focusing on the series minted in 1961. It is argued that the iconography of this series – which stresses the revolutionary merits of Fidel Castro and his movement, and associates the latter with the independence wars – portrays the Castro-led Cuban Revolution as the fulfilment of the nation's aspiration to sovereignty. The article maintains that the design of the 1961 banknote series articulates tropes that convey a fidelista imaginary, presenting the visual rhetoric of currencies as a mechanism of propaganda and persuasion.